Emerging Bluetongue Virus Serotype 4 in the Balearic Islands, Spain (2021): Outbreak Investigations and Experimental Infection in Sheep - David Romero-Trancón; Marta Valero-Lorenzo; María José Ruano; Paloma Fernández-Pacheco; Elena García-Villacieros; Cristina Tena-Tomás; Ana López-Herranz; Jorge Morales; Bartolomé Martí; Miguel Ángel Jiménez-Clavero; Germán Cáceres-Garrido; Montserrat Agüero; et al. (Microorganisms)
Bluetongue is an infectious, non-contagious, arthropod-borne viral disease of ruminants caused by bluetongue virus (BTV), producing severe impacts on livestock. Historically, Southern Europe has suffered multiple incursions of different BTV serotypes with serious consequences. In 2021, BTV re-emerged in the Balearic Islands (Spain) after 16 years free of the disease, causing a large outbreak that mainly affected sheep, as well as cattle and goats. A novel emerging strain of BTV serotype 4 (BTV-4) was identified via preliminary molecular characterization as the etiological culprit of the epizootic. This study delineates the outbreak in the Balearic Islands in 2021, encompassing field-based clinical observations and laboratory findings. Additionally, an experimental infection was conducted in sheep using the novel BTV-4 strain to assess its virulence, pathogenicity, and laboratory diagnostic characteristics. The in vivo characterization was conducted concurrently with the virulent and widely disseminated BTV-4 RNM 2020 strain that has precipitated significant outbreaks in the Mediterranean region in recent years. Both strains exhibited analogous pathogenic potential in sheep and yielded equivalent outcomes in diagnostic parameters. Furthermore, the impact of the novel BTV-4 strain is discussed.